Monitoring of administrative bodies of urban violations in Algerian legislation. - Bouafia, Zineb (Journal of Human Sciences, 2021)
The prevailing urban chaos and the increased need for organized urbanization imposed on the Algerian legislator the enactment of legal texts through which it works to achieve this. The core task in the field of urbanism, which is translated into field outputs, the latter is culminated in records of a mandatory formula distinguished by complete transparency, as it investigates violations and works to deter them. The Algerian legislator strives to achieve the most appropriate space for life, through the decentralization of control, as decentralized bodies are closer to the field and their control is more effective than it is central control, and it also supports these The bodies are in other bodies of a highly technical nature, so that the state can establish oversight in this field with its technical and legal types. In the end, it should be noted that these bodies have made a quantum leap and have begun to perform their duties in good proportions Recently.